Post-conflict risks - Collier, P; Hoeffler, A; Söderbom, M (2006)
Post-conflict societies face two distinctive challenges: economic recovery and risk reduction. Aid and policy reforms have been found to be highly effective in the economic recovery. In this paper we concentrate on the other challenge, risk reduction. The post-conflict peace is typically fragile: around half of all civil wars are due to post-conflict relapses. Both external actors and the post-conflict government must therefore give priority to reducing the risk of conflict. Our statistical results suggest that economic development does substantially reduce risks, but it takes a long time. We also find evidence that UN peacekeeping expenditures significantly reduce the risk of renewed war. The effect is large: doubling expenditure reduces the risk from 40% to 31%. In contrast to these results we cannot find any systematic influence of elections on the reduction of war risk. Therefore, post-conflict elections should be promoted as intrinsically desirable rather than as mechanisms for increasing the durability of the post-conflict peace. Based on these results we suggest that peace appears to depend upon an external military presence sustaining a gradual economic recovery, with political design playing a somewhat subsidiary role. Since there is a simple and statistically strong relationship between the severity of post-conflict risks and the level of income at the end of the conflict this provides a clear and uncontroversial principle for resource allocation: resources per capita should be approximately inversely proportional to the level of income in the post-conflict country.